Magic Angle Effect: A Relevant Artifact in MR Neurography at 3T? - Kästel, T. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: MRN is an emerging diagnostic method for disorders of peripheral nerves. However, it is unclear whether the influence of the MA on intraneural T2 signal is severe enough to provoke false-positive findings. MATERIALS AND METHODS: Twenty-five healthy subjects underwent MRN of the sciatic nerve of the proximal thigh at 3T. The T2(app) was calculated from a DE-TSE sequence (TR = 3000 ms, TE1 = 12 ms, TE2 = 69 ms) at 7 angles of the sciatic nerve relative to B0 = 0°, 30°, 35°, 40°, 45°, 50°, and 55°. Precise angle adjustments were performed with a dedicated in-bore positioning aid. Qualitative evaluation of intraneural T2-weighted contrast between this group of healthy subjects and 14 patients with neuropathic lesions was performed by comparing CNRs of a TIRM sequence (TR = 5000 ms, TE = 76 ms, TI = 180 ms). RESULTS: In healthy subjects, the prolongation of T2(app) from 0° to 55° was from 74.5 ± 13.4 to 104.0 ± 16.9 ms (P < .001). The increase in T2(app) relative to baseline (0°) was 9.6% (30°), 18.4% (35°), 25% (40°), 27.6% (45°), and 37% (55°). Intraneural CNR increased by 1.98 ± 0.69 at 40° and 2.93 ± 0.46 at 55°. Nevertheless, the mean CNR of healthy subjects was substantially lower than that in patients at 40° (P < .0001) and even at the position of maximum MA (55°: 20.6 ± 5.11 versus 52.6 ± 7.12, P < .0001). CONCLUSIONS: Neuropathic lesions are clearly distinguishable from an artificial increase of intraneural T2 by the MA. Even at a maximum MA (55°), the false-positive determination of a neuropathic lesion is unlikely.